2008
DOI: 10.3801/iafss.fss.9-167
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Moisture on Ignition Time of Cellulosic Materials

Abstract: The effect of equilibrium moisture content (ranging from 4 to 12.5% moisture, corresponding to 20 to 90% relative humidity) on piloted ignition times of single wall and tri-wall corrugated paperboard samples has been measured over a range of external radiant heat flux (10 to 60 kW/m 2 ) in the Fire Propagation Apparatus (ASTM E-2058). It has been shown for heat fluxes up to 50 kW/m 2 corrugated paperboard samples behave as thermally thin solids and satisfy a simple fundamental equation based on energy required… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 9 publications
4
19
0
Order By: Relevance
“…12. It has been shown that for heat fluxes up to 50 kW/m 2 corrugated paperboard behaves as a thermally-thin solid at ignition [17]. During this period, experimentally measured exponential fire growth in terms of chemical heat release rate as a function of time, shown in Fig.…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…12. It has been shown that for heat fluxes up to 50 kW/m 2 corrugated paperboard behaves as a thermally-thin solid at ignition [17]. During this period, experimentally measured exponential fire growth in terms of chemical heat release rate as a function of time, shown in Fig.…”
Section: Resultsmentioning
confidence: 94%
“…However, one can assess the role of moisture by using the current model. By changing m w in the model from 0.04 to 0.08 (equilibrium values corresponding to 20 % and 60 % RH) [17], τ g_cal increases about 15 % (see Fig. 9).…”
Section: Effects Of Corrugated Paperboard Properties On τ G_calmentioning
confidence: 99%
See 3 more Smart Citations